AusTraits, a curated plant trait database for the Australian flora. - Daniel,F; Prentice,IC; Gallagher,R; Wenk,E; Bloomfield,K; Dong,N (Scientific Data, 2021)
We introduce the AusTraits database - a compilation of values of plant traits for taxa in theAustralian flora (hereafter AusTraits). AusTraits synthesises data on 448 traits across28640 taxa from field campaigns, published literature, taxonomic monographs, andindividual taxon descriptions. Traits vary in scope from physiological measures ofperformance (e.g. photosynthetic gas exchange, water-use efficiency) to morphologicalattributes (e.g. leaf area, seed mass, plant height) which link to aspects of ecologicalvariation. AusTraits contains curated and harmonised individual- and species-levelmeasurements coupled to, where available, contextual information on site properties andexperimental conditions. This article provides information on version 3.0.2 of AusTraitswhich contains data for 997808 trait-by-taxon combinations. We envision AusTraits as anongoing collaborative initiative for easily archiving and sharing trait data and also providesa template for other national or regional initiatives globally to fill persistent gaps in traitknowledge.